Case Report: Refractory Ventricular Fibrillation Resolved by Double External Defibrillation and Beta Blockade - Humza Khan; Jennifer Campoli; Susan Wojcik (Clinical Practice and Cases in Emergency Medicine)
Introduction: The mortality rate for refractory ventricular fibrillation (RVF) can be up to 97%. There is no widely accepted treatment plan for this stage of ventricular fibrillation besides the standard combination of defibrillation, amiodarone, and epinephrine. One novel approach that has been documented in a select few cases since 2015 is the combination of double external defibrillation (DED) and esmolol-induced beta blockade. Case Report: We report the case of a 65-year-old man who presented with RVF after collapsing at work. Upon the simultaneous administration of two defibrillators with a combined shock of 400 joules and 35 milligrams of the beta blocker esmolol, the patient regained pulse and began blinking. He was discharged from the hospital after seven days and walked out of the clinic. Conclusion: This case continues the trend of several case reports since 2015 that have featured beta blockade and double external defibrillation as a viable solution to refractory ventricular fibrillation. Since there is limited quantifiable data on the efficacy of this treatment, future studies should aim to evaluate whether the combination of DED and beta blockade has the potential to become the new standard in treating RVF over a broader patient population.